NUMERICAL INVESTIGATION OF THE INVERSE NODAL PROBLEM BY CHEBYSHEV INTERPOLATION METHOD - Gulsen, Tuba; Yilmaz, Emrah; Akbarpoor, Shahrbanoo (Vinca Inst Nuclear Sci, 2018)
In this study, we deal with the inverse nodal problem for Sturm-Liouville equation with eigenparameter-dependent and jump conditions. Firstly, we obtain reconstruction formulas for potential function, q, under a condition and boundary data, a, as a limit by using nodal points to apply the Chebyshev interpolation method. Then, we prove the stability of this problem. Finally, we calculate approximate solutions of the inverse nodal problem by considering the Chebyshev interpolation method. We then present some numerical examples using Matlab software program to compare the results obtained by the classical approach and by Chebyshev polynomials for the solutions of the problem.
Keywords: inverse nodal problem; stability; Sturm-Liouville equation; Chebyshev interpolation method; approximate solutions